ANALISIS KELAYAKAN INVESTASI PROYEK PEMBANGUNAN PROPERTI PERUMAHAN DAN PERTOKOAN PADA LAHAN KOSONG DI KABUPATEN CILACAP - , Furqon Sean; , Kusdhianto Setiawan, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The existence of vacant land in Cilacap, which untapped makes that area is little bit lagging economy between regional Middle Java. The vacant land in Cilacap can decrease image and tax. Therefore, there needs developed the vacant land in order to grow the economy. The vacant land is 4000 square meters with frontage is 32 meters and length of land is 125 meters. According to condition of physic and market, that land will be developed residential and commercial property. This research analyzed the feasibility of investment housing complex and commercial property projects of market aspect, physic and legality aspect, and financial aspect. This research found that projects are feasible if the capital structure is equity and debt, and full of debt. Target sale is minimum 70 percent for housing residential project. Target occupancy rate for commercial property project is 80 percent. Reinvestment rate is minimum 3 percent for housing residential project and 0 percent for commercial property project. Not recommended for investor to develop residential with business model in sale. Keywords: vacant land, residential and commercial property, feasibility investment, capital structure, reinvestment rate